Discovery of fecal microbial signatures in patients with ankylosing spondylitis - Yuquan You; Wei Zhang; Meimei Cai; Qingxin Guo; Jiawen Wang; Yaping Cai; Junsheng Lin (Archives of Rheumatology, 2023)
Objectives: This study aimed to investigate the characteristics of the gut microbiota in Chinese patients with ankylosing spondylitis (AS) and healthy controls in Quanzhou aiming to explore the correlation between microbiome changes and AS activities. Patients and methods: In this study, high-throughput sequencing of the gene of 16S ribosomal RNA (16S rRNA) in fecal samples from 40 AS patients and 40 healthy controls, for a total of 80 participants (70 males, 10 females; mean age 33.7±10.7 years; range, 15 to 58 years), was conducted between January 2018 and January 2019. Alpha and beta diversity were analyzed using the QIIME (Quantitative Insights Into Microbial Ecology) software, and differences were analyzed using Student’s t-test, linear discriminant analysis coupled with effect size and Metastats. Finally, a correlation network was constructed using Pearson’s analysis. Results: The alpha index values of the AS group were not significantly different from those of the control group. At the genus level, eight genera, Ruminiclostridium_9, Fusicatenibacter, Adlercreutzia, CAG-56, Intestinimonas, Lachnospira, Bacteroides, and Pseudoflavonifractor, were significantly enriched in patients with AS, whereas the abundance of uncultured_bacterium_f_Saccharimonadaceae, Prevotella_7, uncultured_bacterium_f_ Enterobacteriaceae, Cronobacter, Prevotellaceae_NK3B31_group, and Weissella were significantly decreased in patients with AS. In addition, diseaserelated gut microbial communities were detected in patients with AS. Conclusion: We found differences in the gut microbiome between the patients with AS and controls and identified potential disease activity-related bacterial communities.